Fusion of Lightweight Networks and DeepSort for Fatigue Driving Detection Tracking Algorithm - Kai Xu; Fu Li; Deji Chen; Linlong Zhu; Quan Wang (IEEE Access, 2024)
The fatigue driving detection process faces issues such as a large number of parameters, low accuracy and insufficient continuous detection. To address these, this paper proposes a method combining enhanced YOLOv5s and DeepSort for fatigue driving detection. First, the improved Mobilenet_ECA lightweight backbone is introduced to reconstruct the YOLOv5s backbone part. Then, the CSPDarknet53(C3) module in the neck network is integrated with the Triplet Attention Module (TAM) to enhance the fusion of contextual information and improve the network’s facial feature extraction capability. In addition, FocalEIOU Loss is used to optimize the problem of large errors in Complete Intersection over Union (CIoU) Loss prediction box regression calculations. Next, the DeepSort facial feature tracking algorithm is combined for continuous classification tracking to optimize the problem of driver facial information loss. Finally, the facial feature detection results are combined with the number of consecutive eyeclosed frames, the number of consecutive yawning frames, and the Percentage of Eyelid Closure over the Pupil over Time (PERCLOS) score to build a fatigue driving detection model. The experimental results show that compared with the baseline model YOLOv5s, the algorithm proposed in this article has improved mAP@0.5 and P by 1% and 1.8%, Params decreased by 56.3%, FLOPs decreased by 63.2%, and the model size is only 6.4 MB. The final recognition rate of fatigue and nonfatigue driving was as high as 97.4%. It is verified that the algorithm in this paper can maintain high detection accuracy while being lightweight, and can effectively identify driver states, providing strong support for the deployment of vehicle edge devices.